A Prospective Comparative Study between Dry and Wet Tympanoplasty - Pothala, Hepsiba; Shukla, Sunita Chhapola; Khan, Wasim; Ramalingam, Ravi; Ramalingam, Kombupalayam Komarappa (Annals of Otology and Neurotology, 2018)
Background Tympanoplasty is the well-established procedure for closure of perforations of tympanic membrane.Study Design This study was a prospective comparative study.Objective The objective of this study was to compare the hearing improvement and graft uptake rate between dry and wet tympanoplasty performed on tubotympanic type of chronic suppurative otitis media.Materials and Methods One hundred forty patients with tubotympanic type of chronic otitis media were selected and categorized into dry and wet ears. Tympanoplasty was performed using temporalis fascia by underlay technique in all cases. Postoperatively, graft uptake rate and hearing improvement were analyzed.Results The graft uptake rate was equal in both dry and wet ears, which was statistically insignificant. There was no statistically significant difference in the hearing improvement between the dry ears and wet ears (χ – 2.39, p = 0.122).Conclusion Factors such as age, sex, and status of the contralateral ear and wet ear did not have any impact on the postoperative graft uptake of tympanoplasty. There was no difference in the graft uptake between the dry and wet ears and there was no statistically significant difference between hearing improvement in both and wet ears.
Keywords: chronic suppurative otitis media; dry ear; wet ear; tympanoplasty